Gold Pawn Marketing Strategy to Increase the Number of Customers at Bank Syariah Indonesia KCP Rungkut 1 - Intan Permatasari; Rifa’atul Maftuhah; Fatkur Huda (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the marketing strategy of the gold pawning product (rahn) at BSI KCP Rungkut 1 and its impact on the increase in the number of customers. Using a qualitative approach with a case study method, data were collected through interviews with internal bank representatives. The research findings indicate that the marketing strategies implemented encompass the 7Ps of marketing: a sharia-based product, competitive pricing without interest, active promotion through social media and direct visits to markets ("market raids"), as well as fast, transparent services guided by the AKHLAK values. These strategies have successfully attracted new customers, particularly from the MSME sector and housewives. The number of customers increased from 300 in 2023 to 425 in 2024. This proves that an effective marketing strategy, based on community engagement and sharia principles, can enhance customer trust and loyalty toward the gold pawning product.